The influence of random excitation on parametric oscillations of nonlinear system with one degree of freedom - Thinh, Dang Huu (Vietnam Journal of Mechanics, 1982)
This paper deals with the influence of random excitation a stationary stochastic process on the parametric oscillations in the resonance region of a single – degree of freedom system.